1999
DOI: 10.1177/0739986399213004
|View full text |Cite
|
Sign up to set email alerts
|

Mexican American Women’s Definitions of Rape and Sexual Abuse

Abstract: Focus group approach was used to explore concepts related to rape and sexual abuse among 17 Mexican immigrant women living in rural Arizona. The women discussed definitions of various forms of unwanted sexual experiences, their personal knowledge of someone who had been raped or sexually abused, and their perceptions of the roots of sexual abuse. Distinctions between rapto and violación, child versus adult rape (including marital rape), motivations for rape, and social factors contributing to victim silencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(63 citation statements)
references
References 34 publications
5
58
0
Order By: Relevance
“…Asian cultures are generally reluctant to talk about sex openly and perceive female sexuality as controllable only by the woman's husband. Hispanic notions of decente (that a woman must be pure) and marianismo (ennoblement of female chastity) suggest that Hispanic-American women experiencing sexual assault may come to be viewed as tainted or culpable (Hamilton 1989;Lira et al 1999). Pressure from the cultural community may be a factor contributing to Williams and Holmes' (1981) finding that HispanicAmerican groups have greater difficulty recovering from rape than do Caucasian-Americans.…”
Section: Perceptions Of Victim Injury and Recoverymentioning
confidence: 88%
“…Asian cultures are generally reluctant to talk about sex openly and perceive female sexuality as controllable only by the woman's husband. Hispanic notions of decente (that a woman must be pure) and marianismo (ennoblement of female chastity) suggest that Hispanic-American women experiencing sexual assault may come to be viewed as tainted or culpable (Hamilton 1989;Lira et al 1999). Pressure from the cultural community may be a factor contributing to Williams and Holmes' (1981) finding that HispanicAmerican groups have greater difficulty recovering from rape than do Caucasian-Americans.…”
Section: Perceptions Of Victim Injury and Recoverymentioning
confidence: 88%
“…For instance, religion may help to provide a protective environment and encourage a perception of community support (Sorenson & Siegel, 1992;Sue & Sue, 1999) that may decrease psychological effects for Latinas who have experienced childhood maltreatment, especially sexual abuse. Conversely, it has been suggested that some religious beliefs may heighten victim-blaming responses, which may lower reporting rates and help-seeking by Latina victims, thereby contributing to deleterious psychological effects (Ramos Lira, Koss, & Russo, 1999). Further, Latino cultures tend to hold more traditional values than the US dominant culture (Lefl ey, Scott, Llabre, & Hicks, 1993), including an emphasis on the role of the family.…”
Section: Child Abuse Research With Diverse Populationsmentioning
confidence: 99%
“…An environment of familial support may encourage reporting and, in turn, help prevent long-term negative effects for victims of child maltreatment. In contrast, the traditional family values noted in many Latino populations may decrease reporting rates and victim support, as failure to protect an abusing relative could be considered a dishonor to the family (Ramos Lira et al, 1999).…”
Section: Child Abuse Research With Diverse Populationsmentioning
confidence: 99%
“…This finding is important to examine in future studies with Latina women. Previous research has reported that Latina women view sexual intercourse, even when forced, with their husband or partner as part of their role in the relationship (Lira, Koss, & Russo, 1999); therefore, they may be less likely to report forced sex as IPV. With Latina women's changing role in the household and access to promotoras who provide information about domestic violence and resources, they may be more likely to report forced sex as IPV.…”
Section: Implications For Researchmentioning
confidence: 99%